Understanding and controlling the release mechanism of Escherichia coli in double W1/O/W2 emulsion globules in the presence of NaCl in the W2 phase. Issue 127 (14th December 2015) - El Kadri, Hani; Overton, Tim; Bakalis, Serafim; Gkatzionis, Konstantinos
Abstract : The results suggest that release of bacteria from W1 /O/W2 emulsion can be controlled by varying the formulation. Release occurs due to oil globule bursting independent to diffusion. Abstract : Destabilising the structure of double emulsions can be useful for controlling release of substances at the desirable time. Release mechanisms of encapsulated compounds in double emulsions have been described; however, our understanding of bacterial release is limited and the presence of bacteria may affect the emulsion and vice versa . In this work, the stability and release properties of double W1 /O/W2 emulsions were studied with or without the presence of GFP-tagged Escherichia coli ( E. coli -GFP) in the inner aqueous phase (W1 ) as well as the impact of altering the osmotic balance by adding NaCl in W2 . Double W1 /O/W2 emulsion preparation and E. coli -GFP encapsulation was achieved using a two-step homogenisation process and structure was changed by altering the concentration of hydrophilic surfactant (Tween80, 0.5% to 10%) and W1 (20% and 40%). The release of E. coli -GFP was monitored by culture and observed using fluorescence microscopy. The release of E. coli -GFP was significantly ( P < 0.05) increased when the osmotic balance was altered and the concentration of W1 was high and Tween80 was low. In contrast, no release of E. coli -GFP occurred during osmotic balance alteration when the concentration of W1 was low and Tween80 was high. Bacterial release occurred due to oil globule bursting independent of diffusion mechanisms. Changing the structure of the emulsion can be used for controlling bacterial release in double emulsions which occurs due to the bursting of the oil globules.